(untitled) (Student Conference Proceedings, 2025)
The yield strength is typically determined by performing tensile tests, as material non-linearities preclude accurate estimation in other load cases. Conversely, the objective of this project is to obtain these material parameters from the force-deformation curve of a four-point bending test. To this end, an iterative optimization process was implemented using the finite element method and the programming language R. The SDAR-algorithm is used to determine the Young’s modulus. The estimation of the yield strength and the constant n is achieved through the Ramberg-Osgood-Equation, a model that successfully delineates the stress-strain curve with a mere three parameters. Synthetic test data was used to determine the accuracy of yield strength determination, yielding a relative error of 0.2 %.